Developing a 110‐in. 4K × 2K TV. Issue 6 (1st November 2013) - Chen, Li‐Yi; Chen, Yu‐Yeh; Hou, Hung‐Lung; Mo, Yuming; Chiu, Chung‐Yi
Abstract : China Star has demonstrated a 110‐in. LCD TV that has an outstanding dynamic contrast ratio of 50000:1, ultra‐high brightness of 1000 nits, high‐saturated color reproduction, and a 288‐zone local‐dimming backlight. Manufacturing a high‐definition high‐quality TV in such a large size brings with it special manufacturing challenges.